Empty region identification method and experimental verification for the two-dimensional complex structure. (November 2021) - Dong, Longjun; Tong, Xiaojie; Hu, Qingchun; Tao, Qing
Abstract: Empty region detection has wide-rang application in geotechnical engineering, such as resource exploration and tunnelling engineering. The traditional geophysical exploration methods require plenty preliminary investigations, which are also greatly affected by various parameters and limited by wave velocity difference. Therefore, this paper proposes a new method for empty region identification in the two-dimensional complex structure. It utilizes the improved A* search algorithm to search the shortest wave path, and matches with the potential empty region to estimate the size and position of the cavity. The numerical analysis and laboratory test were carried out to evaluate this method. The effectiveness of the method is proved by the results of holes in the detected area with different diameters, positions and shapes. The reliability of the method is demonstrated by the search results of arrival time difference data with errors. The results of laboratory test further verify the feasibility of the method. This paper provides a new idea for the empty region detection and lays the foundation for three-dimensional empty space detection, which is also suitable for testing of materials and machinery. Highlights: Proposing a straightforward and credible method for empty region identification. Estimating the cavity by searching the shortest wave path and matching with the potential empty region. The validity and reliability of the new method are verified by the numerical examples and the acoustic emission tests.